2008
DOI: 10.1634/stemcells.2008-0634
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Multipotent Epidermal Stem Cells Do Not Protect Their Genome by Asymmetrical Chromosome Segregation

Abstract: The maintenance of genome integrity in stem cells (SCs) is critical for preventing cancer formation and cellular senescence. The immortal strand hypothesis postulates that SCs protect their genome by keeping the same DNA strand throughout life by asymmetrical cell divisions, thus avoiding accumulation of mutations that can arise during DNA replication. The in vivo relevance of this model remains to date a matter of intense debate. In this study, we revisited this long-standing hypothesis, by analyzing how mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 57 publications
4
55
0
Order By: Relevance
“…Pulse-chase experiments involving the halogenated thymidine analog 5-bromo-2-deoxyuridine (BrdU) have been used to label DNA and track label-retaining cells that are growing slowly or asymmetrically dividing (9,(12)(13)(14)(15). Using a strategy similar to that reported for single mitotic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse-chase experiments involving the halogenated thymidine analog 5-bromo-2-deoxyuridine (BrdU) have been used to label DNA and track label-retaining cells that are growing slowly or asymmetrically dividing (9,(12)(13)(14)(15). Using a strategy similar to that reported for single mitotic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetric division of template DNA has been shown in fibroblasts and epithelial, neural, and muscle satellite cells (1,(5)(6)(7)(8)(9)(10). Other studies have demonstrated that hematopoietic stem cells (HSCs), epidermal basal cells, hair follicle bulge cells, and intestinal epithelial stem cells segregate their chromosomes randomly (11)(12)(13)(14)(15). Perhaps asymmetric division of template DNA is cell type-specific, or perhaps only a very limited number of stem cells retain their template DNA strands in some tissues, which may go undetected by the methods or mathematical models used.…”
mentioning
confidence: 99%
“…It has been proposed that SCs may undergo asymmetric divisions during which the SC retains the older ("immortal") DNA strand and the committed daughter cell inherits the newest synthesized DNA strand (Cairns 1975). Double-labeling pulse-chase experiments (Sotiropoulou et al 2008) and chromatin labeling with single uridine labeling provided evidence that in vivo HF SCs segregate their chromosomes randomly. Consistent with the skin barrier function, epidermal SCs are continuously assaulted by UV irradiation.…”
Section: Genomic Maintenance In Epidermal Stem Cellsmentioning
confidence: 99%
“…Bromodeoxyuridine pulse during the early stage of HF regeneration indicates that the first cells to incorporate bromodeoxyuridine are the cells of the hair germ (HG), followed by bulge SCs, suggesting a two-step mechanism of HF regeneration in which the first cells to be activated are the HG cells, followed by bulge SCs (Greco et al 2009). After an initial burst of proliferation that accompanies the early stage of HF regeneration, bulge SCs continue to divide at a lower rate during all of the growing stages of the hair cycle and then stop dividing during catagen (Sotiropoulou et al 2008;Waghmare et al 2008). Lineage tracing of single bulge SCs shows their ability to migrate from the bulge to the HG and their multipotency at a clonal level (Zhang et al 2009b).…”
Section: Bulge Stem Cellsmentioning
confidence: 99%
“…This seems to be true for intestinal epithelium (Potten et al 1978), muscle (Shinin et al 2006), and neural stem cells (Karpowicz et al 2005) but not for hair follicle (Sotiropoulou, Candi, and Blanpain 2008) or hematopoietic (Kiel et al 2007) stem cells. However, it is not clear whether these disparities arise from looking at cells with different specifics in terms of lag between divisions.…”
Section: Molecular Mechanisms Of Asymmetric Divisionmentioning
confidence: 91%